2012
DOI: 10.1103/physrevlett.109.027203
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Bond-Nematic Phase inLiCuVO4

Abstract: Polarized and unpolarized neutron scattering experiments on the frustrated ferromagnetic spin-1/2 chain LiCuVO4 show that the phase transition at H(Q) of 8 T is driven by quadrupolar fluctuations and that dipolar correlations are short range with moments parallel to the applied magnetic field in the high-field phase. Heat-capacity measurements evidence a phase transition into this high-field phase, with an anomaly clearly different from that at low magnetic fields. Our experimental data are consistent with a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
147
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(158 citation statements)
references
References 26 publications
9
147
2
Order By: Relevance
“…66 for explicit calculations. We thus would like to posit that a recent neutron scattering study 67 , which observed longitudinal spin fluctuations but no transverse ones, is very much consistent with SDW phase scenario. Like the spin nematic phase, which is expected to occur at much higher magnetic fields, the SDW phase does not support lowenergy transverse spin excitations.…”
Section: A Implications For Two Dimensionsmentioning
confidence: 99%
“…66 for explicit calculations. We thus would like to posit that a recent neutron scattering study 67 , which observed longitudinal spin fluctuations but no transverse ones, is very much consistent with SDW phase scenario. Like the spin nematic phase, which is expected to occur at much higher magnetic fields, the SDW phase does not support lowenergy transverse spin excitations.…”
Section: A Implications For Two Dimensionsmentioning
confidence: 99%
“…Especially, the so-called spin-nematic state has recently received strong interest [9][10][11][12][13][14] . The spin-nematic phase can be likened to the arrangement of molecules in nematic liquid crystals.…”
mentioning
confidence: 99%
“…Among these compounds, the most often studied is LiCuVO 4 with J 1 = −19 K and J 2 = 44 K [25]. It has been shown using large single crystals that LiCuVO 4 exhibits an incommensurate helical order at low fields [25][26][27][28][29], which may be a 3D analogue of the vector chirality …”
mentioning
confidence: 99%
“…Among these compounds, the most often studied is LiCuVO 4 with J 1 = −19 K and J 2 = 44 K [25]. It has been shown using large single crystals that LiCuVO 4 exhibits an incommensurate helical order at low fields [25][26][27][28][29], which may be a 3D analogue of the vector chirality order in the J 1 -J 2 chain, and a longitudinal SDW order at intermediate fields [26][27][28][29]. Furthermore, a spin nematic phase, a 3D analogue of the spin nematic state, has been suggested slightly below the saturation field of 44.4 T at H c, where the magnetization shows a linear field dependence [30].…”
mentioning
confidence: 99%
See 1 more Smart Citation